Caffeine for apnea of prematurity and brain development at 11 years of age - Claire E. Kelly; Wenn Lynn Ooi; Joseph Yuan‐Mou Yang; Jian Chen; Chris Adamson; Katherine J. Lee; Jeanie L. Y. Cheong; Peter J. Anderson; Lex W. Doyle; Deanne K. Thompson (Annals of Clinical and Translational Neurology, 2018)
Abstract Objective Caffeine therapy for apnea of prematurity has been reported to improve brain white matter microstructure at term‐equivalent age, but its long‐term effects are unknown. This study aimed to investigate whether caffeine affects (1) brain structure at 11 years of age, and (2) brain development from term‐equivalent age to 11 years of age, compared with placebo. Methods Preterm infants born ≤1250 g were randomly allocated to caffeine or placebo. Magnetic resonance imaging (MRI) was performed on 70 participants (33 caffeine, 37 placebo) at term‐equivalent age and 117 participants (63 caffeine, 54 placebo) at 11 years of age. Global and regional brain volumes and white matter microstructure were measured at both time points. Results In general, there was little evidence for differences between treatment groups in brain volumes or white matter microstructure at age 11 years. There was, however, evidence that the caffeine group had a smaller corpus callosum than the placebo group. Volumetric brain development from term‐equivalent to 11 years of age was generally similar between treatment groups. However, there was evidence that caffeine was associated with slower growth of the corpus callosum, and slower decreases in axial, radial, and mean diffusivities in the white matter, particularly at the level of the centrum semiovale, over time than placebo. Interpretation This study suggests any benefits of neonatal caffeine therapy on brain structure in preterm infants weaken over time and are not clearly detectable by MRI at age 11 years, although caffeine may have long‐term effects on corpus callosum development.